Intestinal Barrier Dysfunction in the Absence of Systemic Inflammation Fails to Exacerbate Motor Dysfunction and Brain Pathology in a Mouse Model of Parkinson's Disease - Jackson, Aeja; Engen, Phillip A.; Forsyth, Christopher B.; Shaikh, Maliha; Naqib, Ankur; Wilber, Sherry; Frausto, Dulce M.; Raeisi, Shohreh; Green, Stefan J.; Bradaric, Brinda Desai; Persons, Amanda L.; Voigt, Robin M.; et al. (Frontiers in Neurology, 2022)
Introduction Parkinson's disease (PD) is the second most common neurodegenerative disease associated with aging. PD patients have systemic and neuroinflammation which is hypothesized to contribute to neurodegeneration. Recent studies highlight the importance of the gut-brain axis in PD pathogenesis and suggest that gut-derived inflammation can trigger and/or promote neuroinflammation and neurodegeneration in PD. However, it is not clear whether microbiota dysbiosis, intestinal barrier dysfunction, or intestinal inflammation (common features in PD patients) are primary drivers of disrupted gut-brain axis in PD that promote neuroinflammation and neurodegeneration. Objective To determine the role of microbiota dysbiosis, intestinal barrier dysfunction, and colonic inflammation in neuroinflammation and neurodegeneration in a genetic rodent model of PD [α-synuclein overexpressing (ASO) mice]. Methods To distinguish the role of intestinal barrier dysfunction separate from inflammation, low dose (1%) dextran sodium sulfate (DSS) was administered in cycles for 52 days to ASO and control mice. The outcomes assessed included intestinal barrier integrity, intestinal inflammation, stool microbiome community, systemic inflammation, motor function, microglial activation, and dopaminergic neurons. Results Low dose DSS treatment caused intestinal barrier dysfunction (sugar test, histological analysis), intestinal microbiota dysbiosis, mild intestinal inflammation (colon shortening, elevated MPO), but it did not increase systemic inflammation (serum cytokines). However, DSS did not exacerbate motor dysfunction, neuroinflammation (microglial activation), or dopaminergic neuron loss in ASO mice. Conclusion Disruption of the intestinal barrier without overt intestinal inflammation is not associated with worsening of PD-like behavior and pathology in ASO mice.